Propofol reduces reactive oxygen radical dependent lipid peroxidation after experimental spinal cord injury in rats - (:unkn) unknown (My University, 2007)
Primer omurilik hasarı (OH) sıklıkla önlemez iken; sekonder hasar reaktif oksijen radikalleri (ROR)’nin neden olduğu lipid peroksidasyon (LP)’un azalmasını sağlayan tedavilerle hafifletilebilir. Bu çalışmada, propofol anestezisinin sıçanlarda OH’nda meydana gelen ROR’ne bağlı LP üzerine olan etkisini araştırmayı hedefledik. Otuzdört sıçan rastgele olarak 4 gruba ayrıldılar: Grup L (n=7)’de sadece laminektomi ve Grup T (n=7)’de laminektomiyi takiben OH oluşturulurken; Grup P1 (n=10)’de bolus propofolü yapıldıktan sonra OH ve Grup P2 (n=10)’de ise OH oluşumu sırasında propofol hem bolus hem de infüzyon olarak uygulandı. Omurilik hasarı sonrasında ROR ve LP seviyelerinde belirgin artış olduğu saptandı. Bu artışların her iki propofol grubunda da belirgin olarak azaldığı görüldü. Hem Grup P2, hem de Grup L’deki ROR ve LP değerlerinin Grup P1’ den belirgin düşük olduğı görüldü. Bu sonuçlar propofolün sıçanlarda deneysel OH sonrasında ortaya çıkan ROR’a bağlı LP’u önemli ölçüde azaldığını göstermiştir.

Primary spinal cord injury (SCI) is frequently inevitable; however secondary injury may be ameliorated by treatment that reduces reactive oxygen radical (ROR) dependent lipid peroxidation (LP). In this study, we investigated the effect of propofol on ROR dependent LP subsequent to SCI in anesthetized rats. Thirty four rats were divided into four groups: In Group L (n=7), only laminectomy was performed. In Group T (n=7), after performing laminectomy, SCI was inflicted. In Group P1 (n=10), after bolus propofol injection, the procedure was started and SCI was inflicted following laminectomy. In Group P2 (n=10), propofol bolus plus infusion was maintained throughout laminectomy and SCI procedure. SCI resulted in significant increase in production of ROR and level of LP respectively. These increases were significantly prevented by propofol in both Groups. There were also significant difference between Group P1 and both Groups L and P2 when both production of ROR and the level of LP were evaluated. In conclusion, these results clearly show propofol significantly reduces reactive oxygen radical dependent lipid peroxidation after experimental spinal cord injury in rats.
Propofol, sıçanlarda deneysel omurilik travması sonrasında reaktif oksijen radikallerinin neden olduğu lipid peroksidasyonu azaltmaktadır
Keywords: Nörolojik Bilimler